Fundamental Frequency in Excised Human Larynges after Anterior Glottic Web Formation of Various Extents. (April 2019) - Pinheiro, Thais Gonçalves; Ishikawa, Camila Cristina; Imamura, Rui; Frizzarini, Ronaldo; Montagnoli, Arlindo Neto; Tsuji, Domingos Hiroshi
Objective: To determine the effect of vocal fold anterior web formation on fundamental frequency with a cadaveric excised larynx model. Study Design: Experimental study with excised human larynges. Setting: Academic tertiary care hospital. Subjects and Methods: Sixteen freshly excised human larynges were evaluated with high-speed videoendoscopy and digital kymography during artificially produced vibration. Each larynx was assessed in 4 conditions: preoperative controls and after 25%, 33%, and 50% decreases in the vibratory portion of the vocal folds. The following parameters were evaluated: fundamental frequency, periodicity, vocal fold vibration amplitude, phase symmetry, and glottic closure. Results: The mean fundamental frequencies were 208.87, 250.20, 292.37, and 342.67 Hz for preoperative controls and 25%, 33%, and 50% reductions in vibratory length of the vocal folds, respectively. Fundamental frequency increased with each increase in anterior glottic web extent, and the difference among the groups was statistically significant in absolute values in hertz and in semitone elevation. The mathematical models for estimating postoperative fundamental frequency had a statistically significant coefficient. The vibration of the vocal folds remained periodic in all larynges before and after the procedures. Conclusion: There was a significant and progressive increase in the fundamental frequency with each enlargement of anterior glottic web. Based on the control frequency, mathematical models could estimate the value of the fundamental frequency after the procedure.